The relativity of evaluative sentences: disagreeing over disagreement - Díaz Legaspe, Justina (2013)
Evaluative sentences (moral judgments, expressions of taste, epistemic modals) are relative to the speaker's standards. Lately, a phenomenon has challenged the traditional explanation of this relativity: whenever two speakers disagree over them they contradict each other without being at fault. Hence, it is thought that the correction of the assertions involved must be relative to an unprivileged standard not necessarily the speaker's. I will claim instead that so far, neither this nor any other proposal has provided an explanation of the phenomenon. I will point out several problems presented by them and I will hint to how this phenomenon could be explained by making minor adjustments to our semantic theory.